STABILIZATION OF LINAU VILLAGE SOIL WITH FABA AND CEMENT MIXTURE ON CBR VALUE - Safitri, Nika; Lola Cassiophea; Revianti Coenraad (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2024)
The Palangka Raya - Gunung Mas Provincial Road, Linau Village, Rungan District, Gunung Mas Regency often experiences road damage, this damage is caused by the frequent passage of loaded vehicles such as trucks and timber company trucks that trigger road damage. This study aims to determine the type of native soil and the effect of adding a mixture of fly ash, bottom ash and cement to the soil. This research study is to find the optimum moisture content value of native soil and soil using a mixture percentage of fly ash, bottom ash and cement of 2.5%, 5%, 10%, 15% and 20% respectively. In this research, the work carried out in the laboratory includes testing the physical properties of soil and mechanical properties of soil. The original soil was tested to determine the value of moisture content, specific gravity, sieve analysis, atterbertg limits, soil compaction and, CBR, and mixture testing. The results obtained obtained the soil classification is included in the CL group where the Linau Village soil is non-organic silt and very fine sand, rock powder or fine silty or clayey sand. With an optimum native soil moisture content value of 31.28% and native soil bearing strength CBR of 1.11%. Testing the original soil mixture of fly ash, bottom ash and cement, the most optimum moisture content value is obtained in a mixture of 10% with an optimum moisture content of 13.40% with an optimum soil bearing strength of 95% CBR of 5.37% and 100% CBR of 4.71% .